The Continent Aspect of Orthotopic Neobladder - Alkifaee, Ahmed Abbas Shareef; Al-Ibraheemi , Hayder Maki Baqer; Ali, Walaa Rasheed; Al-Maliki , Shaymaa Jasim Mohammed (American Journal of Biomedicine and Pharmacy, 2025)
Radical cystectomy (RC) remains the reference standard treatment for patients with muscle-invasive bladder cancer and the success of orthotopic urethral anastomosis surgeries has been demonstrated throughout time, thus these options should be presented to all patients who qualified. To evaluate the timing of neobladder continence post-operatively for both diurnal and night continence. During the period from JULY 2019 to OCTOBER 2021, a total of 20 patients with muscle invasive transitional cell carcinoma (TCC) of bladder (15 males and 5 females) who underwent radical cystectomy with orthotopic neobladder, their age between (35-70) years who fulfilled the inclusion criteria and completed at least 1year of follow up. This survey, the diurnal continence rate was 85% 12 months after surgery. The highest rate of nocturnal continence was achieved during follow up at 12 months after surgery is 60%.The mean age of patients who had urine continence was significantly lower than incontinent patients. Diabetes is associated with a poor prognosis for daytime and nighttime continence. RC and orthotopic urine diversion have a very good rates of daytime continence. It's important to focus on resolving nighttime incontinence, which may take more time to be improved. A good, satisfactory functional continence results are achieved after orthotopic urine diversion, and this may be efficiently monitored with a validated questionnaire.